African Philosophy of Religion: Concepts of God, Ancestors, and the Problem of Evil - Cordeiro‐Rodrigues, Luís; Agada, Ada (Philosophy Compass, 2022)
Abstract There has recently been an increased interest in debates on the nature of God, supernatural entities, and the problem of evil outside the Western tradition and there is a growing realisation that philosophical scholarship should go beyond Western perspectives in order to properly address issues in the philosophy of religion that arise in non‐Western cultures. Taking this on board, this article surveys the field of African philosophy of religion and highlights some of the concerns and issues driving debates in the field. In particular, we focus on three important debates. Firstly, we outline the two main schools of thought that divide African philosophers into theistic and non‐theistic camps. We label the theistic perspective the 'African theistic view' and the non‐theistic perpective the 'limited God view'. Secondly, we explore how commitment to the two views has led to distinct explanations of the problem of evil. Thirdly, we highlight the role of ancestors in African belief‐systems and their place in the scheme of things. Adopting the method of philosophical exposition and argument, we show how the two dominant views of God's nature define this emerging field of African philosophy and will determine the future trajectory of the field.
free